2022
DOI: 10.3390/polym14020245
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Synthesis, Curing Behavior and Flame Retardance of a Novel Flame Retardant Curing Agent for Epoxy Resin

Abstract: In this work, a flame retardant curing agent (DOPO-MAC) composed of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO and methyl acrylamide (MAC) was synthesized successfully, and the structure of the compound was characterized by FT-IR and 1H-NMR. The non-isothermal kinetics of the epoxy resin/DOPO-MAC system with 1% phosphorus was studied by non-isothermal DSC method. The activation energy of the reaction (Ea), about 46 kJ/mol, was calculated by Kissinger and Ozawa method, indicating that the curing re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…For L7, porous char residues can be observed, which was resulted from the released inert gases of MCA or pyrolysis products. On the one hand, it destroyed the compactness of the char layer; on the other hand, the released inert gases diluted the oxygen concentration on the surface of the material and thickened the residues as a whole 23,26,27 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For L7, porous char residues can be observed, which was resulted from the released inert gases of MCA or pyrolysis products. On the one hand, it destroyed the compactness of the char layer; on the other hand, the released inert gases diluted the oxygen concentration on the surface of the material and thickened the residues as a whole 23,26,27 …”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, it destroyed the compactness of the char layer; on the other hand, the released inert gases diluted the oxygen concentration on the surface of the material and thickened the residues as a whole. 23,26,27…”
Section: Cone Calorimetry Testmentioning
confidence: 99%
“…To address this issue, a new organic flame retardant containing phosphorus and nitrogen was developed by studying the flame retardant properties of polymers and related mechanisms. [2][3][4][5][6] When a fire occurs, it is not only property damage that ensues but also casualties, making flame retardant research on epoxy resin an essential prerequisite for ensuring its safe and effective use. [7][8][9][10] In recent decades, organohalogen flame retardants have been widely utilized for their low dosage and high efficiency in retarding flames.…”
Section: Introductionmentioning
confidence: 99%
“…However, the flammability of EP limits its potential applications in structural materials for electronic devices, aircraft, and ground vehicles. To address this issue, a new organic flame retardant containing phosphorus and nitrogen was developed by studying the flame retardant properties of polymers and related mechanisms 2–6 . When a fire occurs, it is not only property damage that ensues but also casualties, making flame retardant research on epoxy resin an essential prerequisite for ensuring its safe and effective use 7–10 …”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] There has been reported that the flame-retardant efficiency of DOPO can be further improved through the molecular design method. [16][17][18] Thereinto, introducing the nitrogen-containing group (such as triazine, [19,20] triazinetrione, [21][22][23] Schiff-base, [24][25][26] and hexachlorocyclotriphosphazene [27,28] ) is a feasible way. The phosphophenanthrene group and nitrogen-containing group can exert a P−N synergistic flame-retardant effect to improve the flame retardancy of epoxy thermosets.…”
Section: Introductionmentioning
confidence: 99%